Carbon storage and sequestration potential in aboveground biomass of bamboos in North East India - Angom Sarjubala Devi (Nature Portfolio, 2021)
Abstract The Northeastern hilly states of India harbor nearly 90 species of bamboos, 41 of which are endemic to the region. Estimation of C-storage and C-sequestration in aboveground biomass of two common bamboo species namely Bambusa tulda and Dendrocalamus longispathus was carried out in Mizoram-one of the eight states of Northeastern India. Recording of density of culms was done by quadrate method and harvesting of culms was done to estimate the aboveground biomass. C-storage in different components of the culms was found out for three age classes namely 1, 2 and ≥ 3 year old culms. Aboveground biomass ranged from 73.58 to 127 Mg/ha in Bambusa tulda and 115 to 150 Mg/ha in Dendrocalamus longispathus. Culm density and aboveground biomass were maximum in the ≥ 3 year age class in both the species. C-storage ranged from 36.34 to 64.00 Mg/ha in Bambusa tulda and 50.11 to 65.16 Mg/ha in Dendrocalamus longispathus. Although having lower aboveground biomass the rate of C-sequestration was higher in Bambusa tulda with 27.79 Mg/ha/year than Dendrocalamus longispathus which have 15.36 Mg/ha/year. The reason was attributed to higher increment of culm density and DBH of the older age class in the second year study period in Bambusa tulda.